2006
DOI: 10.1590/s0104-66322006000200009
|View full text |Cite
|
Sign up to set email alerts
|

Application of molecular sieves in the fractionation of lemongrass oil from high-pressure carbon dioxide extraction

Abstract: -The aim of this work was to study the feasibility of simultaneous process of high-pressure extraction and fractionation of lemongrass essential oil using molecular sieves. For this purpose, a highpressure laboratory-scale extraction unit coupled with a column with four different stationary phases for fractionation: ZSM5 zeolite, MCM-41 mesoporous material, alumina and silica was employed. Additionally, the effect of carbon dioxide extraction variables on the global yield and chemical composition of the essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 10 publications
(10 reference statements)
0
17
0
2
Order By: Relevance
“…The differential response of EOs for decay area caused by P. italicum or P. digitatum could be attributed to the components and biological activity of respective oil. Thus, better inhibition of P. digitatum and P. italicum by lemon grass oil may be due to high content of citral (Paviani et al 2006). Irrespective of essential oil treatment and storage, P. italicum caused higher decay area than P. digitaum.…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential response of EOs for decay area caused by P. italicum or P. digitatum could be attributed to the components and biological activity of respective oil. Thus, better inhibition of P. digitatum and P. italicum by lemon grass oil may be due to high content of citral (Paviani et al 2006). Irrespective of essential oil treatment and storage, P. italicum caused higher decay area than P. digitaum.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Differential inhibition of pathogens by EOs may be due to their composition, which contribute to their biological activity. For example, high content of citral (Paviani et al 2006) was found as the main compound in lemon grass oil, while clove oil contains eugenol, caryophyllene, furfurol, α-pinene and eugenyl acetate and eugenol a phenolic compound (70-90 %) was the main contributor (Matan et al 2006), and the antimicrobial activity of eucalyptus essential oil is due to the presence of a mixture of monoterpenes and oxygenated monoterpenes. (Aggarwal et al 2002).…”
Section: Effects Of Eos On Colony Diameter Of Test Pathogensmentioning
confidence: 99%
“…The major component of the essential oil of lemon grass, extracted from the plant grown in Southern Brazil was found to be citral (80-85%). 29 Thus, when a mixture of thiophenol (2a) and the essential oil of lemon grass was submitted to MW irradiation (548W) for 0.5 min in the presence of KF/Al 2 O 3 (50%, 0.07 g), 3,7-dimethyl-3-(phenylthio)oct-6-enal (3a) was obtained in 52% yield, together with unreacted mircene, linalool, geraniol and others minor constituents of the starting oil, that were recovered.…”
Section: Resultsmentioning
confidence: 99%
“…Lemon grass reportedly contains 1% to 2% of essential oil on a dry basis. The oil is usually extracted and used as a raw material in food, cosmetic, and pharmaceutical industries (Paviani et al 2006).…”
Section: Introductionmentioning
confidence: 99%